Does brand capital influence corporate environmental policies? Evidence from toxic release inventory data - Haidar, Md Ismail; Kroll, Mark; Nguyen, Nam H. (Journal of Corporate Finance, 2025)
We investigate the relationship between brand capital and corporate environmental policies using toxic chemical release data. Using a sample of 4752 publicly listed U.S. firm-year observations from 1991 to 2020, we find that brand capital is significantly and negatively related to firm's toxic emissions, suggesting that firms with stronger brand capital tend to exhibit more environmentally responsible behavior. Further evidence reveals that the effect of brand capital on corporate environmental policies is more pronounced for firms in communities that prefer stringent environmental regulations. Additional analysis points to increased financial stability, environmental innovations, and environmental abatement investments as the mechanisms behind the documented effect of brand capital on firms' environmental policies. The results are robust to numerous robustness tests, including the use of alternative measures of brand capital, environmental policies, and several endogeneity tests. The results support the idea that strong brand capital can promote environmental responsibility in firms.